PERAN KELOMPOK TANI SANGKURYANG UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT DALAM PERSPEKTIF EKONOMI ISLAM DESA SAMUSTIDA KECAMATAN TELUK KERAMAT - Kiki Siti Rohani (CV. Adiba Aisha Amira, 2025)
This research is motivated by one of the government's efforts with farmers to build their independence, namely by forming farmer groups in rural areas. Efforts to increase farmers' human resources can be carried out through a learning process through guidance, counseling, training, field studies, mentoring and so on which must be adapted to farmers' needs and farmers' abilities in accordance with the situations and conditions faced by farmer groups. This research aims to determine the form of farmer groups, namely to empower farmers so that the farming activities carried out by farmers can develop and achieve prosperity for all its members evenly in Samustida Village, Teluk Keramat District. Technological updates or new innovations need to be carried out by farmer groups to increase income from rice fields, agricultural products and plantation areas. The approach used is a qualitative approach. This type of research is field research. The location of this research is the Sangkuryang Farmers Group in Samustida Village, Teluk Keramat District. Data collection uses interview, observation and documentation methods. The data sources obtained consisted of primary data sources and informants, 1 person accompanying the farmer group, 20 members of the secondary data farmer group. The results of this research show that the role of the Sangkuryang farmer group is: 1) Very helpful in improving the welfare of the community in fulfilling the assistance received from the government, namely a rice grinding machine and then we built a rice mill and tractor. 2) very helpful in increasing rural development based on the results of deliberations that have been agreed upon jointly through community representatives in the village. 3) improving community welfare, efforts to improve welfare must begin by identifying problems that hinder the effort itself, then start revitalizing these problems by formulating appropriate policies. 4) helping farmers so that the farming activities carried out by farmers continue to develop and achieve welfare of all its members equally